If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -15) + -1(2x + -13) = 1 Reorder the terms: (-15 + x) + -1(2x + -13) = 1 Remove parenthesis around (-15 + x) -15 + x + -1(2x + -13) = 1 Reorder the terms: -15 + x + -1(-13 + 2x) = 1 -15 + x + (-13 * -1 + 2x * -1) = 1 -15 + x + (13 + -2x) = 1 Reorder the terms: -15 + 13 + x + -2x = 1 Combine like terms: -15 + 13 = -2 -2 + x + -2x = 1 Combine like terms: x + -2x = -1x -2 + -1x = 1 Solving -2 + -1x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 1 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 1 + 2 -1x = 1 + 2 Combine like terms: 1 + 2 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3
| 6x(6x)+5(3x(3x)-x)-3x= | | 4x-3+90=180 | | f(x)=500-75x | | 3x(x-2)=24 | | 3x(x-2)=23 | | (1+0.05)4= | | A=0.5(b+12)5 | | 2x-6+2x-9=180 | | 9+x+7+x=50 | | 2-3(x-5)=20 | | 23x=10x+5 | | 4-y=230 | | 4x=18+4 | | 10x=5x+2 | | 5(3)=3645 | | (11x*2/3)*(11x*-2/3) | | 19-a=-2a | | 2x-27=95 | | 10-6x=20-26x | | 3x^2-4x+119=0 | | 70-2x=85-3x | | 4/d=12 | | y^2-8y+154=0 | | 4x-32=3x+10 | | -0.33-m=-0.11m+0.037-0.33m | | -40=(x-10) | | 10-4x=30-44x | | -2(-2)-4(-2)= | | 323=-1+6(8a+6) | | 84-2x=98-3x | | -2x-2-4(-2)= | | 2-7(m-8)=114 |